Desempeño profesional para la inclusión educativa en el nivel educación inicial - Manssur Baus, Jamile Uidé (2023)
In the present research work, an arduous bibliographic review can be verified, which has fundamental authors for the development of teaching together with scientific articles, virtual books and national and international research works, which serve as documentary support for the author of this work to carry out the description and analysis for the development of the theme which is "professional performance for educational inclusion atthe initial education level". At the beginning of the investigation, the incident factors in the problem are established, which focus on teacher performance and its impact on the inclusive approach at the initial level II (Kindergarten), taking into account the importance of training, motivation and vocation. constant that professionals in this field of teaching must have in order to be able to respond to the needs, not only in the classroom, but also in the social ones of the time inwhich the profession is developed.............